Walter Abbott Wood (1907-1993) - Wood, Peter H. (ARCTIC, 1994)
Approximately 70 years ago a young man developed a deep and very personal relationship with the mountain world and a keen interest in the scientific investigation of its natural wonders. . His successful academics and his mountain prowess led Wood to the American Geographical Society in New York City, where in the 1930s he directed the Society's Department of Exploration and Field Research. It was at the AGS that he conceived of and developed a program of exploration and scientific research that was to evolve during the rest of his life. . During World War II, Walter Wood played a leadership role in the development of military logistic support techniques in the high mountains and participated in the training of mountain troops, first while at the U.S. Army's Arctic, Desert, Tropic Information Center in Minneapolis and later in cooperation with Canadian military personnel, . The Wood Yukon expeditions of the 1930s had been forerunners to a far more sophisticated scientific examination of the St. Elias Mountains in the decades following World War II. . Project Snow Cornice encompassed four field seasons: 1948, 1949, 1950 (winter) and 1951. . Wood in 1961 founded the Icefield Ranges Research Project (IRRP), again under the auspices of the Arctic Institute of North America together with the American Geographical Society. . In recalling and recounting the highlights of these expeditions and field research programs, it is easy to take their success for granted. At the same time, we should be very much aware that although the successes shine brightly, they came as the result of not only a great amount of hard work, but most especially because of the extraordinary vision, organizational ability and leadership of Walter Wood. Wood, as a geographer, was a great believer in coordination and cooperation among sciences and scientists. . He was a marvellous leader of both his scientific and his mountaineering companions. .